2008
DOI: 10.1007/s10147-007-0730-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastasis from renal cell carcinoma without inferior vena involvement: a review of the literature based on a case report. Two different patterns of spread?

Abstract: We report the case of a 59-year-old man with advanced renal cell carcinoma (RCC), without inferior vena cava (IVC) involvement, treated with radical nephrectomy, palliative radiotherapy for bone metastasis, and medical therapy for bone and lung metastases. The patient died of cardiac arrest after evidence of massive malignant pericardial effusion. At autopsy, massive myocardial and pericardial neoplastic invasion was found. Heart involvement via the IVC is a well-known phenomenon during RCC progression, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 16 publications
(4 reference statements)
1
33
0
Order By: Relevance
“…The first employs a venous haematogenous pathway through the renal vein to the right heart. In patients with isolated disease and delayed disease progression to the right heart, with no involvement of the IVC, microdissemination through a venous haematogenous pathway remains the most probable mode of metastasis 1315. The second is through the lymphatic vessels of the thorax, and then through the reversed lymphatic flow caused by metastasis to the nodes, metastatic RCC can spread to the pericardium and the left myocardium 1517.…”
Section: Discussionmentioning
confidence: 99%
“…The first employs a venous haematogenous pathway through the renal vein to the right heart. In patients with isolated disease and delayed disease progression to the right heart, with no involvement of the IVC, microdissemination through a venous haematogenous pathway remains the most probable mode of metastasis 1315. The second is through the lymphatic vessels of the thorax, and then through the reversed lymphatic flow caused by metastasis to the nodes, metastatic RCC can spread to the pericardium and the left myocardium 1517.…”
Section: Discussionmentioning
confidence: 99%
“…However, cases without vena cava involvement have also been described [8,9,10]. In these cases, it has been suggested that RCC metastasizes to the heart via the lymphatic system [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The right atrium [7] and the right ventricle of the heart are common sites for RCC spread via the inferior vena cava [6]. However, cases without vena cava involvement have also been described [8,9,10]. In these cases, it has been suggested that RCC metastasizes to the heart via the lymphatic system [10].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor may involve the pericardium and less frequently, myoendocardium.So malignant pericardial effusion is a common finding in advanced cancer patients (Kim et al, 2010). Although uncommon, there are reports of malignant pericardial effusion secondary to RCC (Zustovich et al, 2008).…”
Section: Cardiac Manifestationsmentioning
confidence: 99%